What Is the Suitable Wide Cage Size for Stand-alone LLIF in Asian Population: A Computed Tomography Scan–Based Study of a Dimension of Lumbar Endplate - Pluemvitayaporn, Tinnakorn; Tadee, Sahapap; Kunakornsawat, Sombat; Surapuchong, Suttinont; Ratanakoosakul, Warot; Tiracharnvut, Kijapat; Pruttikul, Pritsanai; Piyasakulkaew, Chaiwat; Kittithamvongs, Piyabuth (Asian Journal of Neurosurgery, 2024)
Objective The objective of this study is to establish a precise database detailing the width of vertebral endplates, the depth of vertebral endplates (anterior–posterior [A-P] width), and the height of intervertebral discs within the lumbar spine of the Asian population.Materials and Methods The stand-alone lateral lumbar interbody fusion (LLIF) procedure is increasingly popular for minimally invasive spine surgery and has demonstrated effectiveness in treating various spinal pathologies. Previous studies have indicated that the use of a 26-mm wide cage in stand-alone LLIF can significantly decrease the incidence of cage subsidence. However, most of these studies were conducted on the Caucasian population, which has a larger anatomical structure compared with the Asian population. Consequently, the appropriate wide cage size suitable for stand-alone LLIF in the Asian population has not been previously explored. Ninety-one computed tomography (CT) images were obtained from patients who presented with back pain and had negative imaging results between 2017 and 2021. These images were analyzed using the Picture Archiving Communication System to assess the vertebral body's topography. The analysis involved measuring the vertebral endplate width, vertebral endplate depth (A-P width), and intervertebral disc height.Results The findings of this study reveal that there is a noticeable increase in the overall width, depth, and intervertebral disc height of the lumbar vertebrae from the upper to the lower regions. Additionally, the morphometric attributes of the lumbar vertebrae observed in this study closely resemble those of Caucasian subjects.Conclusion The morphometric measurements of the lumbar vertebrae in the Asian population closely resemble those of Caucasian subjects. As a result, it is suggested that a 26-mm wide cage may be a suitable option for stand-alone LLIF in the Asian population.
Keywords: stand-alone LLIF; lateral lumbar interbody fusion; lumbar spine; dimension; lumbar endplate diameter